2015
DOI: 10.1002/2015wr017888
|View full text |Cite
|
Sign up to set email alerts
|

Stream water age distributions controlled by storage dynamics and nonlinear hydrologic connectivity: Modeling with high-resolution isotope data

Abstract: To assess the influence of storage dynamics and nonlinearities in hydrological connectivity on time‐variant stream water ages, we used a new long‐term record of daily isotope measurements in precipitation and streamflow to calibrate and test a parsimonious tracer‐aided runoff model. This can track tracers and the ages of water fluxes through and between conceptual stores in steeper hillslopes, dynamically saturated riparian peatlands, and deeper groundwater; these represent the main landscape units involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
205
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(230 citation statements)
references
References 67 publications
22
205
3
Order By: Relevance
“…Our simulations emphasize the time-variant character of water ages and travel times in hydrological systems, as observed at the catchment scale in various recent studies (van der Velde et al, 2012;Benettin et al, 2013;Heidbüchel et al, 2013;Soulsby et al, 2015;Benettin et al, 2017). Further, the age dynamics in the soil waters were driven by the variability in water stored in the soils, supporting an "inverse storage effect" as discussed by Harman (2015).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our simulations emphasize the time-variant character of water ages and travel times in hydrological systems, as observed at the catchment scale in various recent studies (van der Velde et al, 2012;Benettin et al, 2013;Heidbüchel et al, 2013;Soulsby et al, 2015;Benettin et al, 2017). Further, the age dynamics in the soil waters were driven by the variability in water stored in the soils, supporting an "inverse storage effect" as discussed by Harman (2015).…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, the rooting zone covered the entire soil profile for the forested sites and down to 15 cm soil depth for the heather site, which affected the resulting travel times and water ages of T accordingly. Investigation of water ages in the ET flux is relatively new (Botter et al, 2011) and age dynamics have usually been assessed for the bulk ET flux (Harman, 2015;Soulsby et al, 2015;van der Velde et al, 2015;van Huijgevoort et al, 2016;Soulsby et al, 2016). While it was shown that tracer-aided modelling using stable isotopes of water benefits from partitioning ET into a fractionating E flux and a non-fractionating T flux (Knighton et al, 2017), separate water age analyses for E and T have been considered only recently (Smith et al, 2018).…”
Section: What Controls Travel Times and Water Ages In Evapotranspiratmentioning
confidence: 99%
See 1 more Smart Citation
“…As an illustrative example we take a simple model from Birkel et al (2010) and Soulsby et al (2015).…”
Section: Appendix C: An Example Of Generalization To Many Embedded Rementioning
confidence: 99%
“…2 in Soulsby et al, 2015). The lower reservoir is responsible for groundwater description and represents a large storage which also has the function of dumping the solute concentration.…”
Section: R Rigon Et Al: Age-ranked Hydrological Budgets and A Travementioning
confidence: 99%